Two-year experience of multi-disciplinary team (MDT) outcomes for brain metastases in a tertiary neuro-oncology centre. (2nd January 2018) - Loh, Daniel; Hogg, Florence; Edwards, Penelope; MacColl, Jillian; Brogna, Christian; Bhangoo, Ranjeev; Ashkan, Keyoumars; Vergani, Francesco
Abstract: Brain metastases (BMs) are the most common intracranial tumour in adults and form a significant proportion of the neuro-oncology workload. Their management has progressed significantly in the last few decades but a gold-standard evidence-based management strategy has not been defined to date and several guidelines based on available evidence exist to support clinical decision-making. This paper evaluates the decision-making process of the neuro-oncology multi-disciplinary team (MDT) in a tertiary neuro-oncology centre over a two-year period. A retrospective review of all patients with BM discussed in the MDT was conducted. Data on patient demographics, tumour characteristics and MDT decision were collected from the MDT database, clinical notes and imaging studies. Patients were stratified into the three recursive partitioning analysis (RPA) classes and according to the graded prognostic assessment (GPA) score. MDT decisions were analysed by RPA class and for GPA score as well as single versus multiple BM. There were 362 patients with BM, representing 22% of the total cases discussed at the MDT. Decision-making was largely consistent with available guidelines. A concrete treatment decision was reached in 77.5% of patients and 32.2% of these received neurosurgical input. More patients with solitary BM underwent surgery compared to multiple BM ( p  = 0.001), and more patients in RPA classes I and II had surgical resection compared to class III ( p  = 0.005 and 0.001, respectively). Surgical patients also had higher GPA scores compared to palliative patients ( p  = 0.005). A greater absolute number and proportion of patients in RPA class II vs. class I underwent neurosurgical intervention. These patients were stratified into class II because of their age but would otherwise have been placed into class I. Survival data were available for 195 patients (53.8%) at 1 year post MDT discussion. A pattern of declining survival was observed along RPA classes which was statistically significant ( p  = 0.0025). Median survival was 4.7 (0–41), 3.7 (0–23), and 2.5 (range 0–24) months for RPA class I, II and III respectively. A similar pattern that did not reach statistical significance was found between GPA scores ( p  = 0.101). Median survival was 3 (0–13), 4.6 (range 0–41), and 4.6 (0–35) months for GPA scores 0–1.0, 1.5–2.5 and 3–4.0, respectively. Patient selection was generally in accordance to RPA class and GPA scoring, with the exception of surgery offered to elderly patients: this can be explained by the increasing number of otherwise fit patients as population ages.